EMERGING TECHNO-POLITICAL AFFORDANCES: TRANSFORMATION OF TECHNICAL AFFORDANCES ON TIKTOK DURING PROTESTS IN PERU - Lopez del Pozo, Melanie Jessica (AoIR Selected Papers of Internet Research, 2026)
This study examines how TikTok’s functional affordances transformed into political affordances during the 2022–2023 protests against Dina Boluarte in Peru. In a context of state repression and media control, TikTok emerged as a vital space for symbolic resistance, where citizens—particularly young content creators—disputed official narratives that criminalized protests.Drawing on digital everyday politics and relational affordance theory, this research employs a mixed-methods approach, including a technical walkthrough of TikTok, content analysis of 286 videos, and interviews with eight content creators. Findings reveal two key political affordances: $2 and $2 . $2 emerged as users leveraged TikTok’s immediacy and editing tools to document repression in real-time, countering state narratives. Protesters became citizen reporters, combining firsthand footage with expressive tools like filters, subtitles, and music to construct alternative accounts of police violence. Meanwhile, $2 arose as TikTok’s algorithm allowed dissident content to reach wider audiences beyond traditional media’s gatekeeping. Creators repurposed TikTok’s viral culture to expose state abuses and mobilize digital activism.These findings demonstrate that affordances are not fixed but dynamically reconfigured in response to political urgencies. TikTok’s technical possibilities were reshaped by protestors’ communicative needs, turning the platform into a space for contestation and resistance. By highlighting how marginalized voices use digital tools to challenge repression, this study contributes to broader discussions on platform politics and social movements in the Global South.